Pelatihan dan Pendampingan Pembuatan Media Pembelajaran Berbasis Quizizz pada Guru di MTs Darul Hikmah Lenggo-Lenggo - Irmayanti Irmayanti; Nurjannah Nurjannah; Mirna Mirna; Hamka Hamka (IAIN AMBON, 2022)
Improving the quality of learning is the responsibility of a teacher and one way is to improve the quality of learning media. One of the free flatforms that teachers can use in the digital age is Quizizz because it has many interesting features. This community service was carried out at Mts Darul Hikmah Lenggo-Lenggo Sinjai Regency. The general purpose of the implementation of this devotion is to improve the understanding and skills of teachers in the learning process in the digital era. The method of service carried out is training and mentoring related to the creation of Quizizz-based learning media. Its implementation began with the introduction of the Quizizz application and its features were then continued with training and mentoring in creating Quizizz-based learning media. As a result of this training and devotion, Mts Darul Hikmah Lenggo-Lenggo teachers have been able to create Quizizz-based learning media in the form of only materials, quizzes only, or combining materials with quizzes, and teachers have been able to concentrate by dividing the learning media links that have been made by their respective subjects. Quizizz-based media created can be accessed anytime and anywhere without limits and paper.Keywords: Training, Mentoring, learning media, Quizizz